Linking brain tumors and epileptic seizures. (November 2018) - Mulcahy Levy, Jean; McMahon, Martin
Mutationally activated BRAF-V600E influences the behavior of different types of cells in the brain and leads to promotion of seizures as well as brain tumors, indicating how both can be pharmacologically targeted in the clinic.